Fear of Cancer Recurrence: Lived Experiences of Cancer Survivors’ Spouses - Urbutienė, Eglė; Pukinskaitė, Rūta (Psichologija, 2022)
Fear of cancer recurrence is the most prevalent and burdensome emotional concern among cancer survivors’ spouses after treatment. This qualitative study aimed to disclose, what are cancer survivors’ spouses lived experiences of fear of cancer recurrence. Seven adult spouses were explored. Data were obtained using a semi-structured interview and analyzed by inductive thematic analysis. Analysis revealed that fear of cancer recurrence is interpersonal experience and fear transmits in a couple. The spouses associate cancer recurrence with death and risk of losing their spouse. The threat of cancer recurrence triggers not only the feelings of insecurity, uncertainty about the future and loss of control, but also appreciation of life. Planning and control, religiosity, avoidance and awareness of fear helped spouses to reduce concerns about relapse. Interventions for spouses should focus on promotion of emotional expression of cancer recurrence concerns, also learning to accept and tolerate uncertainty.
Keywords: cancer; fear of cancer recurrence; spouses